School of the pauper: student’s family per capta income and policies of affirmative action and permanency as a factor of social protection at Instituto Federal do Mato Grosso (IFMT) (Research, Society and Development, 2020)
The institutions of the Federal Network of Professional, Scientific and Technological Education (RFEPCT) since 1909, have assumed, above all, the transforming commitment in society by training humble citizens into qualified workers through professional education. Considering the maintenance of this precept in the RFEPCT, it is questioned, then, if the Federal Institute of Mato Grosso (IFMT) welcomes, in fact, young people belonging to low-income families and focuses the supply of professional education and the development of their activities in that target audience. This paper aims to analyze the per capita family income of IFMT students by comparing them to the Human Development Index (HDI) and Gross Domestic Product (GDP) data per capita of the municipalities that host the 14 campuses and 05 advanced campuses. The methodological procedures adopted to achieve this aim were bibliographic and documentary research, by means of a survey of official institutional sources and the IBGE database. The results showed that, in 2016, the institution served 64.5% of students belonging to low-income families, with a per capita family income below 1.5 minimum wages. From that period, it adopted the inclusion / access / permanence policies, through the institutionalization of the quota system, allocating 60% of its places to students from public schools and, among these, to people with disabilities and self-declared browns, blacks and Indians. Thus, it has sought to promote the social insertion of low-income youth and contribute to the growth and development of regions in the state of Mato Grosso.